Perilaku Kolektif Masyarakat Adat dalam Terbentuknya Pasubayan Desa Adat Bali Tolak Reklamasi Teluk Benoa Tahun 2016 - Suryadana, Putu; Noak, Piers Andreas; Ali Azhar, Muhammad (Jurnal Nawala Politika, 2021)
ABSTRACT Benoa Bay reclamation plan in Bali gave rise to a resistance movement. The movement came from traditional villages in Bali who reject the government policy to reclaim Benoa Bay.The villages that refused the reclamation of Benoa Bay formed a Pasubayanof Traditional Villages of Bali as a platform and means to achieve a common goal of rejecting and nullifying the policy of the reclamation. This research explains how the collective behavior of indigenous people in the formation of Pasubayan in 2016.The theories applied were the Social Interactionist/Behaviorist or Sociocybernetic Theory by McPhail and the Value-Added Theory by Smelser. Through a qualitative approach, data collection techniques were conducted with observation, interview, and documented studies. This study yielded the finding that there is a collective behavior of the indigenous people that formed Pasubayan. Based on the analysis, there is a process in collective behavior that Pasubayan formed. Keywords: Reclamation, Collective Behavior, Pasubayan